Flexural strength of palm oil clinker concrete beams - Mohammed B.S.; Foo W.L.; Abdullahi M. (Elsevier Ltd, 2023)
This paper presents an experimental program on the flexural behaviour of reinforced concrete beams produced from palm oil clinker (POC) aggregates. POC is obtained from by-product of palm oil milling. Utilisation of POC in concrete production not only solves the problem of disposal of this solid waste but also helps to conserve natural resources. An experimental work was conducted involving eight under-reinforced beams with varying reinforcement ratios (0.34-2.21%) which were fabricated and tested. The data presented include the deflection characteristics, cracking behaviour and ductility indices. It was found that although palm oil clinker concrete (POCC) has a low modulus of elasticity, the test results revealed that the deflection of singly reinforced POCC beams, with reinforcement ratio less than 0.524, under the design service load is acceptable as the span-deflection ratios range between 250 and 257 and these values are within the allowable limit provided by BS 8110. In addition, the results reported in this paper indicate that the BS8110 based design equations can be used for the prediction of the flexural capacity of POCC beams with reinforcement ratio up to 2.23%. © 2013 Elsevier Ltd.